FAKTOR RISIKO KEJADIAN STUNTING PADA BALITA DI PUSKESMAS TEGAL SARI KOTA MEDAN: RISK FACTORS FOR STUNTING AMONG CHILDREN UNDER FIVE AT PUSKESMAS TEGAL SARI MEDAN CITY - Rahmadhani, Mayasari; Ayu, Mayang Sari; Damanik, Rosa Zorayatamin; Hasibuan, Hardy (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
This study aims to analyse the risk factors associated with stunting among children under five in the working area of Puskesmas Tegal Sari, Medan City. Stunting remains a serious public health problem caused by early maternal marriage, low maternal education, and suboptimal exclusive breastfeeding practices. This research employed an analytical case-control design using primary data collected through interviews and anthropometric measurements of 20 respondents (10 cases and 10 controls). Data were analysed using Chi-Square and logistic regression tests. The results revealed that early maternal marriage, low education, and lack of exclusive breastfeeding were significantly associated with stunting (p<0.05). The most dominant factor was the absence of exclusive breastfeeding, with an odds ratio (OR) of 3.7. It is concluded that social and educational interventions targeting young mothers, as well as strengthening support for exclusive breastfeeding, are essential to reduce stunting prevalence. AbstrakPenelitian ini bertujuan untuk menganalisis faktor risiko kejadian stunting pada balita di wilayah kerja Puskesmas Tegal Sari Kota Medan. Stunting masih menjadi masalah kesehatan masyarakat yang serius akibat pernikahan dini ibu, rendahnya pendidikan, dan tidak optimalnya pemberian ASI eksklusif. Penelitian menggunakan desain analitik case control dengan data primer dari wawancara dan pengukuran antropometri pada 20 responden (10 kasus, 10 kontrol). Analisis data dilakukan dengan uji Chi-Square dan regresi logistik. Hasil menunjukkan bahwa usia pernikahan dini, pendidikan ibu rendah, serta tidak diberikannya ASI eksklusif berhubungan signifikan dengan kejadian stunting (p<0,05). Faktor paling dominan adalah tidak diberikannya ASI eksklusif dengan OR=3,7. Disimpulkan bahwa intervensi sosial dan edukatif pada ibu muda dan peningkatan dukungan terhadap pemberian ASI eksklusif sangat penting untuk menekan angka stunting.